Design and fabrication of young coconut jelly peeling machine - Iskandar Shah, Muhammad Haziq Lutfi (2025)
The use of young coconut jelly is very popular among people worldwide. The young coconut jelly often used in food and beverages product. The method of peeling the young coconut jelly has been an innovation from year to year. Many innovations product has been in the market to make the process of peeling the young coconut jelly easier. This project was initiated to design and fabricate young coconut filling peeler machine. The purpose of the design was to make the process of peeling the jelly of the young coconut easier so that it can save more energy and make the work faster. The design was based on the electric coconut scrapper machine and the portable coconut scrapper that has blade with the addition of holder and safety mechanism. With this, the blade will peel the young coconut jelly automatically while the holder will hold the coconut so that the person that use this machine will not hold the coconut while the peeling process is ongoing. The purpose of the safety mechanism is to add safety to the person that operating this machine. This machine uses a rod to rotate the blade and scoop that will peel the young coconut jelly. Motor is used to move the rod in rotational motion.